Spadin Selectively Antagonizes Arachidonic Acid Activation of TREK-1 Channels - Ma, Ruolin; Lewis, Anthony (Frontiers in Pharmacology, 2020)
TREK-1 channel activity is a critical regulator of neuronal, cardiac and smooth muscle physiology and pathology. The antidepressant peptide, spadin, has been proposed to be a TREK-1-specific blocker. Here we sought to examine the mechanism of action underlying spadin inhibition of TREK-1 channels. Heterologous expression in Xenopus laevis oocytes and electrophysiological analysis using two-electrode voltage clamp in standard bath solutions was used to characterise the pharmacological profile of wild-type and mutant murine TREK-1 and TREK-2 channels using previously established human K2P activators; arachidonic acid (AA), cis-4,7,10,13,16,19-Docosahexaenoic acid (DHA), BL-1249 and cinnamyl-3,4-dihydroxy-α-cyanocinnamate (CDC) and inhibitors; spadin and barium chloride (Ba2+). Mouse TREK-1 and TREK-2 channel currents were both significantly increased by AA, BL-1249 and CDC, similar to their human homologues. Under basal conditions, both TREK-1 and TREK-2 currents were insensitive to application of spadin, but could be blocked by Ba2+. Spadin did not significantly inhibit either TREK-1 or TREK-2 currents either chemically activated by AA, BL-1249 or CDC, or structurally activated via a gating mutation. However, pre-exposure to spadin significantly perturbed the subsequent activation of TREK-1 currents by AA, but not TREK-2. Furthermore, spadin was unable to prevent activation of TREK-1 by BL-1249, CDC or the related bioactive lipid, DHA. Spadin specifically antagonises the activation of TREK-1 channels by AA, likely via an allosteric mechanism. Lack of intrinsic activity may explain the absence of clinical side effects during antidepressant therapy.